Synthesis of polymer-montmorillonite nanocomposites by in situ intercalative polymerization - Zeng, Q.H.; Wang, D.Z.; Yu, A.B.; Lu, G.Q.
Two polymer-montmorillonite (MMT)nanocomposites have been synthesized by in situ intercalative polymerization. The styrene monomer is intercalated into the interlayer space of organically modified MMT, a layered clay mineral. Upon the intercalation, the complex is subsequently polymerized in the confinement environment of the interlayer space with a free radical initiator, 2,2-azobis isobutyronitrile. The aniline monomer is also intercalated and then polymerized within the interlayer space of sodium- and copper-MMT initiated by ammonium peroxodisulphate and interlayer copper cations respectively. X-ray diffraction indicates that the MMT layers are completely dispersed in the polystyrene matrix and an exfoliated structure has been obtained. The resulting polyaniline-MMT nanocomposites show a highly ordered structure of a single polyaniline layer stacked with the MMT layers. Fourier transform infrared spectra further confirm the intercalation and formation of both polymer-MMT nanocomposites.